Managing Turnover Intention in Healthcare : Implications of Job Satisfaction, Job Stress, and Managerial Support on Retention Strategies: (Case Study of Nur Hayati Hospital, Garut Regency) - Arvi Iskandar (International Journal of Economics and Management Sciences, 2025)
Turnover Intention influenced by a combination of individual, organizational, and work environment factors. In this context, psychological theories such as Herzberg's two-factor theory can help understand this dynamic by dividing factors that influence job satisfaction into motivators and hygiene factors. Motivators, such as recognition and achievement, contribute to higher job satisfaction, while hygiene factors, such as working conditions and management policies, play a role in preventing dissatisfaction. This study aims to explore the relationship between job satisfaction, job stress, managerial support, and employee engagement on turnover intention in various sectors. This study uses a quantitative approach with a Likert scale-based survey to collect data, which were analysed using Pearson correlation tests and multiple linear regression. The results showed that job satisfaction and managerial support have a significant negative relationship with turnover intention, while job stress shows a significant positive relationship. In addition, employee engagement through organizational citizenship behaviour (OCB) has been shown to reduce turnover intention even though the level of job satisfaction is low. This study provides practical implications for organizations to design employee retention strategies through stress management, increasing job satisfaction, and managerial support. This study contributes to the enrichment of the literature on human resource management, particularly in understanding the dynamics of turnover intention, and recommends further research with a longitudinal approach to validate the results in other sectors.